In vitro anticancer effects of frankincense and its nanoemulsions for enhanced cancer cell targeting - Al-Balushi, Rayya A.; Chaudhuri, Aiswarya; Kandimalla, Raghuram; Haque, Ashanul; Alenezi, Khalaf M.; Saeed, Mohd.; Changez, Mohammad; Al Harthy, Thuraya; Al Hinaai, Mohammed; Siddiqui, Samra; Agrawal, Ashish Kumar; Aqil, Farrukh (Frontiers in Pharmacology, 2025)
IntroductionFrankincense has demonstrated promising in vitro anticancer activity. However, its conventional delivery methods face significant challenges due to limited oral bioavailability. To address these limitations, this study focuses on developing optimized nanoemulsions (NEs) of Frankincense oil (FO) to enhance its therapeutic efficacy.MethodsFrankincense resins were extracted and characterized using gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-mass spectrometry (LC-MS), identifying key metabolites including isopinocarveol, α-thujene, p-cymene, carvone, germacrene A, and various methyl esters. FO-based nanoemulsions (FO-NEs) were prepared and optimized using a 3-factor, 3-level Box-Behnken Design (BBD), with 10% FO (v/v), 40% surfactant (cremophor EL), and co-surfactant (Transcutol P). The optimized FO-NEs were evaluated for particle size, polydispersity index (PDI), zeta potential, and morphology using scanning electron microscopy (SEM) and atomic force microscopy (AFM). Cytotoxicity, wound healing, mitochondrial membrane potential (MMP), and reactive oxygen species (ROS) assays were performed against breast cancer (MDA-MB-231, MDA-MB-231-TR) and lung cancer (A549, A549-TR, H1299) cell lines.ResultsThe optimized FO-NEs exhibited an average particle size of 65.1 ± 4.21 nm, a PDI of 0.258 ± 0.04, and a zeta potential of −22.3 ± 1.2 mV. SEM and AFM confirmed the spherical morphology of the FO-NEs. In vitro cytotoxicity studies revealed enhanced anticancer activity of FO-NEs (IC50 = 13.2 μg/mL) compared to free FO (IC50 = 22.5 μg/mL) against resistant breast cancer MDA-MB-231-TR cells. FO-NEs significantly improved cancer cell internalization, disrupted mitochondrial membrane potential, and increased ROS generation, leading to enhanced cytotoxic effects.DiscussionThe results demonstrate that nanoemulsion-based delivery significantly enhances the bioactivity and cellular uptake of frankincense oil compared to its free form. FO-NEs exhibit potent anticancer activity, particularly against drug-resistant cancer cell lines, suggesting their potential as a viable strategy for improving the therapeutic efficacy of frankincense in cancer treatment.